Prominent alumni / Ajurah Hailah ... [et al.] - Hailah, Ajurah; Sikau, Ann Nickline; Wasilie, Nurul Ain; Sid, Rostella (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
That dream came true late Saturday for the ‘so happy and emotional’ senior lecturer of Universiti Teknologi Mara (Mara) Sarawak’s Faculty of Business Administration when he outperformed Chaipipat Liwtrakul of Thailand and Fathuhulla Mohamed of Maldives in the Men’s Athletic Physique 160cm category.